“We have to say no to coal”: Facebook framings of the Egyptians against Coal movement - Moneer, Aziza (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
The study aims to explore and analyze the core collective action frames that were developed by the environmental movement of ‘Egyptians against Coal’ to raise the public awareness about the dangers of coal and mobilize action. The framing theory is used as the main theoretical approach in this study. The study relies on a qualitative content analysis of the Facebook page of ‘Egyptians against Coal’ and interviews conducted with the page creators and activists. The study revealed that by using Facebook, the anti-coal movement managed to make salient new meanings of coal as part of a wider social problem, rather than an ‘economic panacea’ to Egypt’s industry challenges and to phrase frames that resonate with shared political and economic grievances and dominant cultural values in Egypt. In this regard, it was found that the Facebook page constructed four prevalent frames in order to shape public discourse: coal as an environmental disaster, coal and health risks, coal and environmental injustices and socioeconomic costs, and fossil fuel versus renewable energies.